Penerapan Logika dan Algoritma Pemrograman untuk Meningkatkan Keamanan Data Warga Desa Rantau Panjang dalam Sistem Informasi Desa - Harianto, Ozi; Rifqo, Muhammad Husni; Alam, RG Guntur; Juhardi, Ujang (SINTA Journal (Science, Technology, and Agricultural), 2024)
Current advances in technology and information are always related to all human activities. Computers are very important to make human work easier because they can manage data faster than humans. This research aims to protect the data of Rantau Panjang village residents, which is a very important data source, from the village information system using the AES (Advanced Encryption Standard) algorithm. The developmental method is used to solve this research problem. This method aims to determine growth patterns or changes over time. This research was completed using Xampp and Notepad++. This study found that the AES (Advanced Encryption Standard) algorithm can keep citizen data in village information systems safe. The result is that a cryptographic method that uses the AES algorithm in the PHP programming language can help keep citizen data in the village information system more secure. The AES algorithm is a powerful data security algorithm that can be used in the PHP programming language when developing applications. A deep understanding of cryptographic techniques and the use of the AES algorithm in PHP is required.